Childhood maltreatment and decision-making autonomy in adulthood: The mediating roles of self-esteem and social support. (July 2022) - Islam, Md Jahirul; Broidy, Lisa; Eriksson, Li; Rahman, Mosiur; Mazumder, Nurunnahar
Abstract: Background: Childhood maltreatment (CM) is connected with a large number of maladaptive long-term outcomes. Effective prevention and intervention hinges partly on our understanding of the key mediating mechanisms that help account for the relationship between child maltreatment and its long-term consequences. We know the consequences of CM can extend into adulthood, including the intergenerational transmission of violence, re-victimization, high-risk behavior, and persisting mental health problems. We argue that CM also likely affects decision-making autonomy in adulthood, limiting their independence and exaggerating their risk for other poor outcomes. We suggest that the effects of CM on self-esteem and access to social support mediate this relationship, helping to explain how and why CM impacts autonomy in the long term. Objective: This study aimed to examine these relationships using a cross-sectional sample of currently married women of Bangladesh aged 15–49 years ( N  = 426). Method: A multi-stage random sampling technique was employed for data collection and a multivariate logistic regression technique was applied for data analysis. Results: Results from the multivariate logistic regression model revealed a direct effect of a history of CM on limited decision-making autonomy in adulthood and a full mediating effect of self-esteem and social support on the associations between CM and decision-making autonomy in women, even after adjusting for theoretically and empirically relevant covariates. Conclusions: The study findings provide insight into the mechanisms by which early childhood experiences impact autonomous decision-making. However, causality cannot be determined because of the cross-sectional design. Finally, our findings suggest that the influence of CM on autonomy could be augmented by self-esteem recovery through social support from family, friends, and peers.